Potential biocontrol agent of indigenous Bacillus sp. EG6.4: Molecular identification, larvicidal toxicity, and mechanism of actions - SALAMUN SALAMUN; RIZKY DANANG SUSETYO; FARAH AISYAH NAFIDIASTRI; RIZKI AMALIAH ZAIN; ROSSY PERMATA SARI; ALMANDO GERALDI; FATIMAH FATIMAH; NI’MATUZAHROH NI’MATUZAHROH (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Salamun, Susetyo RD, Nafidiastri FA, Zain RA, Sari RP, Geraldi A, Fatimah, Ni’matuzahroh. 2022. Potential biocontrol agent of indigenous Bacillus sp. EG6.4: Molecular identification, larvicidal toxicity, and mechanism of actions Biodiversitas 23: 5431-5438. This research was carried out for molecular identification, as well as the determination and mechanism of action of larvicidal toxicity of Bacillus sp. EG6.4 isolated from breeding sites of Aedes aegypti from Gresik, East Java, Indonesia. Bacillus sp. EG6.4 was a Gram-positive endospore-forming bacteria. Molecular species identification using 16S rRNA gene sequencing showed that isolate had 97.89% similarity with Bacillus mojavensis. The isolate showed larvicidal toxicity against A. aegypti larvae. The lethal concentration 50% (LC50) values ??at 24 and 48hours exposure were 8.99±1.01 ×107 cells/mL and 8.43±1.01 ×107 cells/mL, respectively, while lethal time 50% (LT50) value was 11.9±1.1 hours. Production of chitinolytic enzymes or biosurfactants, chitinolytic and hemolytic assays were conducted to determine the larvicidal mechanism. As a result, Bacillus sp. EG6.4 showed hemolytic, but not chitinolytic activity, indicating its potency to produce biosurfactants. Transmission Electron Microscopy (TEM) result showed that isolate had oval-shaped endospores located subterminal with massive-shape parasporal inclusions. The detection of srfA-D gene showed that isolate produced surfactin biosynthesis thioesterase. Thus, Bacillus sp. EG6.4 produced biosurfactant that potentially to be developed as a biocontrol agent for disease vectors and plant pathogens.